Film size-dependent bias voltage regulated resistance switching behavior for ultra-thin Fe65Co35 films on Pb(Mg1/3Nb2/3)O3–PbTiO3 piezoelectric substrates. (May 2023) - Ma, Meibing; Han, Yemei; Yin, Xin; Shen, Kaisong; Hu, Kai; Sun, Zheng; Wang, Fang; Wu, Haitao; Zhang, Kailiang
Abstract: We report the film size dependent bias voltage modulated resistance switching behavior for a novel memory cell, constructed with ultra-thin Fe65 Co35 (FeCo) thin films grown on Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 (PMN-PT) single crystal piezoelectric substrates. Measurement results show that the PMN-PT exhibits good ferroelectric properties and excellent piezoelectric performance. The saturation polarization intensity and piezoelectric displacement are 35.5 μC/cm 2 and 80 Å, respectively. The PMN-PT/FeCo heterostructure shows a clear magnetic hysteresis loop with a coercive field of 114 Oe and FeCo films possess ferromagnetic domain structures. By applying a bias voltage in the thickness direction of the heterostructure, the current-voltage (I–V) characteristics of the FeCo films on the PMN-PT could be adjusted, and multiple resistance states are generated. The FeCo film size dependence of resistance switching behaviors was investigated by analyzing the resistance change of the samples, a maximum resistance change of 61.5% was obtained for the heterostructure with 100 μm × 100 μm FeCo films, at a bias voltage of 30 V. It is revealed that the resistance switching behaviors of the heterostructures has been enhanced by using small lateral size FeCo films. The memory device can directly write information and data by using an electric field, and read information by using the change of resistance. Highlights: Film size effect on voltage modulated resistance switching behavior is investigated. Memory cells are prepared with Fe65 Co35 films on Pb(Mg1/3 Nb2/3 )O3 –PbTiO3 substrates. A maximum resistance change of 61.5% is obtained for 100 μm × 100 μm Fe65 Co35 film cell.